Changeability and flexibility of assembly line balancing as a multi-objective optimization problem - Fisel, Johannes; Exner, Yannick; Stricker, Nicole; Lanza, Gisela (Journal of manufacturing systems, 2019)
•Trade-off between cost, flexibility and changeability as an optimization problem.•Stochastical dependency of assembly tasks influences variance of assembly times.•Modular bottom up model for equipment reallocation cost.•Changes in the variant mix beyond available flexibility activate changeability. Current trends, such as customers' demand for individual products and shorter product life cycles, are addressed by companies through a greater variety of products and variants. With regard to the line balancing of flow assembly systems, however, adjustments are associated with high investments, which requires a new planning approach for assembly line balancing. Existing approaches do not consider the reallocation of assembly tasks or the dimensioning of system-inherent flexibility and changeability according to requirements. Furthermore, they neglect the uncertainty of the future market situation. The proposed approach aims at optimizing the line balancing of flow assembly systems, taking into account the potential need for adaptation in order to meet this uncertain planning environment. For this purpose, the exchange of occurring costs as well as flexibility and changeability of the system is focused. Based on scenarios, potential future compositions of the variant mix are investigated and the resulting implications for the assembly system are derived. By applying the approach, an adequate adaptable assembly line balancing is generated by performing a mixed integer linear optimization. Since the evaluation and identification of adequacy are subject to subjective factors, several potentially adequate solutions are generated, which differ in terms of costs, flexibility and changeability. The result of the presented approach is a front of pareto-optimal assembly line balancing configurations. In order to show its practical applicability, a use case in automotive assembly line balancing is presented.